UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI PERMAINAN KARTU HURUF - Utami, Muji (Jurnal Likhitaprajna, 2018)
Based on observations made in the first class of SDN Coban Blimbing 2, the majority of students cannot read. Namely, of the 34 students who were able to recognize letters only 40% of the remaining students were 60% who were able to recognize letters but could not yet read. This condition is caused when in learning teachers rarely use teaching aids that can help students to make it easier to recognize letters, words and sentences. This study uses a class action research design (CAR). The average value of students always increases every cycle, which is from 50.00% in the first cycle, up to 70.60% in the second cycle and in the third cycle to 88.23%. This shows that learning through letter card games can improve learning outcomes of class I students of SDN Coban Blimbing 2.Keywords: reading skills, media of learning, letter card games